NATURAL NOCARDIOSIS IN CATTLE: A SURVEY AND PATHOLOGIGIAL STUDY - ALWAN, M. J. (The Iraqi Journal of Veterinary Medicine, 2000)
This work was done to investigate Nocardiosis in cattle in order to evaluate the incidence of nocardiali mastitis in Al- dejiala station, bacteriological examination was conducted on 90 milk samples obtaited from mastitic cows Nocardia asteroides was found in 25 out of 90 (27. 77% mastitic cows. This M.O was recorered in pure culture in 5. cases and as mixed with other microorganisms in 20 cases . The gross examination of the affected udders showed multiple nodular lesions in firm fibrotic udders, some of them formed draining sinus which exuded pus to the exterior multifocal nodules of varying size were seen in the lungs Microscopic examination of the affected udders revealed pyogranulomatous lesions in different areas of the glandular parenchyma multiple classical granulomatous lesions were also noticed in the lung tissues.